2017
DOI: 10.4103/ijpc.ijpc_52_17
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nutritional deficiencies in cerebral palsy compounding physical and functional impairments

Abstract: Introduction:Cerebral palsy (CP) refers to a spectrum of disorders causing physical and intellectual morbidity. Macro and micro nutrient deficiencies often contribute to the subnormal physical and mental capabilities of them.Objectives:To assess the growth, nutritional status, physical and functional ability and quality of life in cerebral palsy children and to determine any relation with their gross motor and functional capabilities.Method:The study was conducted at a Tertiary Care Centre, with the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
2
7
0
1
Order By: Relevance
“…This finding contradicts one of our hypothesis, which proposed that children who used more adaptations would be more functional. However, it is consistent with the findings from other studies that reported an association between lower gross motor function, use of more adaptations, and more assistance provided by the caregiver in self-care and mobility activities (Alghamdi et al, 2019; Hariprasad et al, 2017; Østensjø et al, 2005; Sawyer et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…This finding contradicts one of our hypothesis, which proposed that children who used more adaptations would be more functional. However, it is consistent with the findings from other studies that reported an association between lower gross motor function, use of more adaptations, and more assistance provided by the caregiver in self-care and mobility activities (Alghamdi et al, 2019; Hariprasad et al, 2017; Østensjø et al, 2005; Sawyer et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…20 Another study explained this situation as a disturbance in growth hormone (GH) release. 21 A severe brain damage in CP patient may cause this disruption in normal GH secretion 22 and may affects growth and development of CP patient in various way.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that vitamin B is a class of significant nutrient that highly benefit neurological system, and vitamin B complex in low-doses promote the development, maturation, and enlargement of human embryonic brain cells [26]. Actually, vitamin B complex deficiency has been noted in children with cerebral palsy [27], and the effects of vitamin B1 and B12 on facilitating the regeneration of the peripheral have been previously confirmed [28]. Regretfully, seldom progress has been made in cerebral palsy treatment with vitamin B.…”
Section: Discussionmentioning
confidence: 99%